2019
DOI: 10.1128/mra.01703-18
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Shewanella sp. Strain TH2012, Isolated from Shrimp in a Cultivation Pond Exhibiting Early Mortality Syndrome

Abstract: Here, we present the complete genome sequence of a Shewanella isolate, TH2012, from a shrimp pond in which shrimp exhibited early mortality syndrome (EMS)/acute hepatopancreatic necrosis disease (AHPND). The complete genome of TH2012 has a prophage-like element and a number of potential virulence factors, making TH2012 a possible contributing factor to EMS outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…This was supported by differential morphological and physiological characteristics (Table and Supporting information). Recently, an independent phylogenomic analysis of our published TH2012 T genome sequence (Wechprasit et al , ) also supported this erection of a new species within the genus (Thorell et al , ). Thus, we propose the name Shewanella khirikhana to indicate that TH2012 T originated from Prachuap Khirikhan Province, Thailand.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…This was supported by differential morphological and physiological characteristics (Table and Supporting information). Recently, an independent phylogenomic analysis of our published TH2012 T genome sequence (Wechprasit et al , ) also supported this erection of a new species within the genus (Thorell et al , ). Thus, we propose the name Shewanella khirikhana to indicate that TH2012 T originated from Prachuap Khirikhan Province, Thailand.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, the TH2012 T genome contains a putative prophage (Fig. ) (Wechprasit et al , ) and some virulence genes found in some Shewanella isolates (Paździor, ; Yousfi et al , ) such as putative haemolysins, chitinases and proteases (Wechprasit et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations